2015
DOI: 10.1016/j.jss.2015.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Microparticles impact coagulation after traumatic brain injury

Abstract: Background The pathophysiology that drives the subacute hypercoagulable state commonly seen after traumatic brain injury (TBI) is not well understood. Alterations caused by TBI in platelet and microparticle (MP) numbers and function have been suggested as possible causes; however, the contributions of platelets and MPs are currently unknown. Materials and methods A weight-drop technique of TBI using a murine model of moderate head injury was used. Blood was collected at intervals after injury. MP enumeration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 39 publications
1
37
0
2
Order By: Relevance
“…Further, although rates of VTE are heavily debated, autopsies have shown pulmonary embolism (PE) rates up to 35% (38) and PE-related mortality rates as high as 40% (11). Microparticles are known contributors to hypercoagulability in various disease processes (18, 19, 39), and previous research has demonstrated that PMPs are associated with increased procoagulant activity in fresh frozen plasma (40) and are associated with hypercoagulability in other injury models (22). The current study is the first to highlight the link between PMPs and coagulation in burns and future burn care may require targeted anticoagulation strategies based on the time course after injury, including use of agents that target platelets and PMPs specifically, to more effectively prevent thrombosis-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, although rates of VTE are heavily debated, autopsies have shown pulmonary embolism (PE) rates up to 35% (38) and PE-related mortality rates as high as 40% (11). Microparticles are known contributors to hypercoagulability in various disease processes (18, 19, 39), and previous research has demonstrated that PMPs are associated with increased procoagulant activity in fresh frozen plasma (40) and are associated with hypercoagulability in other injury models (22). The current study is the first to highlight the link between PMPs and coagulation in burns and future burn care may require targeted anticoagulation strategies based on the time course after injury, including use of agents that target platelets and PMPs specifically, to more effectively prevent thrombosis-related morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Clotting time (CT), clot formation time (CFT), clot lysis (LI30), α-angle (AA), and maximum clot firmness (MCF) were determined for each test. Platelet contribution to clot strength (%MCFPlatelet) was calculated by the equation: (EXTEM MCF − FIBTEM MCF )/EXTEM MCF , similar to the methods previously described (20, 22). All analyses were initiated within 10 min of whole blood collection.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the weight of the falling cylinder varies from 5 g to 500 g, and the drop height varies from 1 cm to 167 cm. [13][14][15][16] As a consequence, the biochemical outcome-i.e., the expression of inflammatory cytokines, such as tumor necrosis factor (TNF)-a, interleukin (IL)-6, IL-12, and IL-1b, is highly variable. [17][18][19][20][21] Controlled cortical impact and fluid percussion injury models, procedures that need a craniotomy, induce comparable high cytokine expression.…”
Section: Introductionmentioning
confidence: 99%
“…С другой стороны, активированные тромбоциты формируют агрегаты и могут способствовать блокаде микрососудистого русла и ишемическому повреждению нейронов [12]. Кроме того, прокоагулянтная активность тромбоцитарных микрочастиц, системно возрастающая после травмы головного мозга, может стать причиной посттравматического тромбоза и способствовать развитию атеросклероза сосудов головного мозга [13,14]. Известно, что антитромбоцитарная терапия (например, применение аспирина), широко применяемая для лечения последствий инсульта, препятствует повышенному тромбообразованию, но повышает риск кровотечений.…”
Section: тромбоциты и мозговое кровотечениеunclassified